British Politycal Thought in History, Literature and Theory, 1500 1800 - Armitage, David (Cambridge University Press, 2013)
The field of research and teaching known as the history of British political thought has been one of the most fertile areas in anglophone historical scholarship of the last half-century. Its practitioners can be found in universities across the English-speaking world and increasingly beyond it as well. Their writings have provided prescriptions of method as well as models of practice for students of political thought working in other languages and on other political traditions, even those which were founded on different philosophical principles and which have developed along quite distinct historical trajectories